2014
DOI: 10.1039/c3ee41664j
|View full text |Cite
|
Sign up to set email alerts
|

Improving the electrochemical performance of layered lithium-rich transition-metal oxides by controlling the structural defects

Abstract: We report the electrochemical properties of layered lithium-rich Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 cathode materials with various degrees of stacking faults, which are prepared via a facile molten-salt method using a variety of fluxes including KCl, Li 2 CO 3 , and LiNO 3 . The frequency of the stacking faults is highly dependent on the temperature and molten salt type used during the synthesis. A well-crystallized Li 1.18 Mn 0.54 Ni 0.13 Co 0.13 O 2 nanomaterial with a larger amount of stacking faults synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 31 publications
3
96
0
2
Order By: Relevance
“…[34,35] As indicated previously, the electrode with a hollow structure can accommodate the volume change during repeated Li + insertion/extraction, which is crucial for cycling performance. [9,[36][37][38][39] tion method with excellent rate capability and cyclability. [9] Nevertheless, they only reported that LNMO has good electrochemical properties at room temperature, but the performances at elevated temperature have not been discussed.…”
Section: Introductionmentioning
confidence: 98%
“…[34,35] As indicated previously, the electrode with a hollow structure can accommodate the volume change during repeated Li + insertion/extraction, which is crucial for cycling performance. [9,[36][37][38][39] tion method with excellent rate capability and cyclability. [9] Nevertheless, they only reported that LNMO has good electrochemical properties at room temperature, but the performances at elevated temperature have not been discussed.…”
Section: Introductionmentioning
confidence: 98%
“…In this regard, a class of layered transition metal oxides, namely, the lithium-rich layered oxides (shorted as LLMO) of the general formula xLi 2 MnO 3 ·(1-x)LiMO 2 (M = Mn, Ni, Co) have attracted much attention, which are reported to deliver 230−285 mAh g -1 reversible capacity, reaching nearly the theoretical one e -/metal capacity of the transition metal dioxide [6][7][8][9][10][11][12]. The electrochemical performance of the LLMO materials is strongly dependent on the synthesis technique [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…2019, 6, 1802114 is confirmed by the X-ray photoelectron spectroscopy (XPS) analysis in Figure S7, Supporting Information. [6,44,48] As illustrated in Figure 3f, the prolonged cycles (120 cycles) of LMR oxide cathodes have been promoted dramatically by the uniform Na + -doping and defective structures; the electrode of Na/SDS-LMR maintain 93.1% of capacity (221.5 mAh g −1 ) at 0.5C rate after 200 cycles while only 64.8% (139 mAh g −1 ) is retained for the pristine-LMR. Compared with the pristine-LMR, the activation effect is alleviated in Na-LMR and even disappears completely in Na/SDS-LMR, which originates from the good contact of solid-liquid interface and the large specific surface area.…”
Section: Resultsmentioning
confidence: 98%